2022
DOI: 10.3389/fimmu.2022.887972
|View full text |Cite
|
Sign up to set email alerts
|

CCL5 Release by CCR9+ CD8 T Cells: A Potential Contributor to Immunopathology of Primary Sjögren’s Syndrome

Abstract: IntroductionIncreased CCL5 expression and CD8 T cells have been shown to be pivotal regulators of immunopathology in primary Sjögren’s syndrome (pSS) and pSS-like disease. Increased CCL5 expression by CCR9+ CD4 T cells has previously been implicated as a contributor to immunopathology in pSS. The role of CD8 T cells and in particular CCR9+ CD8 T cells and their potential to secrete CCL5 has not previously been studied in pSS. In this study we investigated both CCR9 and CCL5 expression by CD8 T cells in pSS pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Earlier work from our group and others has shown increased CCR9 expression on CD4 and CD8 T cells in pSS compared to HC ( 21 24 ). In this study we confirmed these findings (representative dot plots in Figure 2A ).…”
Section: Resultsmentioning
confidence: 51%
See 2 more Smart Citations
“…Earlier work from our group and others has shown increased CCR9 expression on CD4 and CD8 T cells in pSS compared to HC ( 21 24 ). In this study we confirmed these findings (representative dot plots in Figure 2A ).…”
Section: Resultsmentioning
confidence: 51%
“…Currently, it is unclear to what extent CD8 T cells and CD8 MAIT cells contribute to immune activation in pSS patients. Nonetheless, it was observed that CD8 T cells were found to associate with lymphocyte aggregates and Tfh numbers in salivary glands of pSS patients ( 24 ). Hence, we anticipate that increased CD8 MAIT cells may also significantly contribute to immune activation in the glandular lymphocytic foci given their effector profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RANTES, also known as CCL5, is a chemotactic cytokine, recruiting leukocytes to the site of inflammation ( Appay & Rowland-Jones, 2001 ). The chemokine CCL5 is mainly expressed by T-cells and monocytes and is abundantly expressed by epithelial cells, fibroblasts, and thrombocytes ( Hinrichs et al, 2022 ). One study found that low levels of RANTES are associated with mortality in children with cerebral malaria ( John et al, 2006 ), suggesting that RANTES has a positive role in counteracting infection.…”
Section: Discussionmentioning
confidence: 99%